Measuring judicial independence the political economy of judging in Japan - Ramseyer, J. Mark, 1954-; Rasmusen, Eric. (Chicago, [Ill.] : University of Chicago Press, 2003)
The Japanese Constitution, like many others, requires that all judges be 'independent in the exercise of their conscience and bound only by this Constitution and its laws'. Consistent with this requirement, Japanese courts have long enjoyed a reputation for vigilant independence - an idea challenged only occasionally, and most often anecdotally. But in this book, J. Mark Ramseyer and Eric B. Rasmusen use the latest statistical techniques to examine whether that reputation always holds up to scrutiny - whether, and to what extent, the careers of lower court judges can be manipulated to political advantage.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Judges -- Japan; Judicial process -- Japan; Political questions and judicial power -- Japan; Courts -- Japan; Law; Japan; Jurisprudence & general issues; Laws of specific jurisdictions & specific areas of law; Legal systems: courts & procedure